GAS-CHROMATOGRAPHIC ELECTRON-IMPACT CHEMICAL-IONIZATION MASS-SPECTROMETRIC IDENTIFICATION OF CINMETACIN AND ITS METABOLITES IN HUMAN URINE - MYUNG, SW; KIM, MS; YOON, CN; PARK, JS; AHN, WS (ELSEVIER SCIENCE BV, 1994)
Cinmetacin and its three metabolites were identified by gas chromatography-electron-impact positive-ion chemical ionization-negative chemical ionization mass spectrometry. After a single oral dose of 30 mg of cinmetacin to a healthy man, urine was collected and hydrolysed. The three metabolites were identified as O-desmethylated, N-descinnamoyl and C-C double bond reduced cinmetacins. The identification of cinmetacin metabolites in human urine was established by comparison of their GC retention times and electron impact and methane chemical ionization mass spectra with those of the synthesized authentic standards.
Keywords: INDOMETHACIN